The origins of nomadic pastoralism in the eastern Jordanian steppe: a combined stable isotope and chipped stone assessment. (2nd September 2018) - Miller, Holly; Baird, Douglas; Pearson, Jessica; Lamb, Angela L.; Grove, Matt; Martin, Louise; Garrard, Andrew
Abstract : The circumstances in which domestic animals were first introduced to the arid regions of the southern Levant and the origins of nomadic pastoralism have been the subject of considerable debate. Nomadic pastoralism was a novel herd management practice with implications for the economic, social and cultural development of Neolithic communities inhabiting steppe and early village environs. Combining faunal stable isotope and chipped stone analyses from the eastern Jordanian Neolithic steppic sites of Wadi Jilat 13 and 25, and 'Ain Ghazal in the Mediterranean agricultural zone of the Levantine Corridor, we provide a unique picture of the groups exploiting the arid areas.